COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE OF SPECIAL HAJJ TRIPS, TRIPS UMRAH AND HALAL TRAVEL TOUR AT PT BIOTA WISATA TOUR & TRAVEL PERIOD 2018-2022 - Arminda Makria Unan; Sultan Sarda; Alamsjah, Alamsjah (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to examine the comparison of financial performance between Special Hajj, Umrah and Halal Tour trips at PT Biota Wisata Tour & Travel for the 2018-2022 period. The variables used to compare financial performance are Current Ratio (CR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Long Term Debt to Equity Ratio (LDR), Net Profit Margin (NPM), Operating Profit Margin (OPM), Return On Equity Ratio (ROE), and Total Asset Return Over (TATO). This type of research is comparative research and the research sample is in the form of financial reports from 3 travel activities, namely Special Hajj, Umrah and Halal Tour. The sample was selected based on travel business activities at PT Biota Wisata Tour & Travel. The analytical method used is analysis of liquidity, solvency, profitability and activity ratios and a two-average difference test (Independent Sample test). The results of research using the difference between two means test show that there is no significant difference in financial ratios consisting of CR, DAR, DER, LDR and ROE between Special Hajj, Umrah and Halal Tour trips at PT Biota Wisata Tour & Travel during the research period. Meanwhile, NPM, OPM and TATO have significant differences between the three in the research period. Overall, the financial performance of Halal Tour trips is better than Special Hajj and Umrah trips at PT Biota Wisata Tour & Travel in the research period.